Brazil's Awa tribe, the final battle - Laurent, Richard (France, 2014)
The Awá tribe of Brazil is facing slow and inevitable destruction. The tribe, around 350 persons, is among the last hunter-gatherers in the world. The forest which they depend upon to survive is shrinking and the Brazilian government, reluctant to take on the powerful agricultural lobby is doing very little to stop them.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films